MODELING THE ELECTRIC POWER SYSTEM OF UKRAINE AND ASSESSING ITS RESILIENCE UNDER CONDITIONS OF SYSTEMATIC TERRORIST ATTACKS - Saukh, S.Ye; Borysenko, A.V. (Tehnìčna elektrodinamìka, 2025)
The analysis of the destructive impact of the periodic massive missile and drone attacks on the electric power system of Ukraine is carried out. The consequences of the attacks are represented in terms of the characteristics of the destruction of typical power industry facilities. Each of these characteristics reflects the distribution of the number of destroyed facilities according to the scale of the destruction: small, medium, and large-scale. The dependence of the duration of repair works on the scale of destruction represents the repair works of destroyed facilities of a certain type. The dynamics equations of sets of power units of different types available for the current period of time could be written on the basis of the introduced characteristics of destruction of power units and the duration of their repair. The damaged NPPs, TPPs, HPPs, damaged PSPPs, and damaged renewable energy facilities comprise the units which have been directly damaged and the units which have lost the ability to work in parallel with the power grid due to the destruction of substations and/or other critical network equipment. In order to study the resilience of the Ukrainian power system to large-scale missile and drone strikes, we have proposed a cluster optimization model of the load modes of typical power equipment, supplemented with the dynamics equations of subsets of this equipment that can be used in current period. This model provides a solution to the problem of predicting the readiness of the electric power system of Ukraine to fulfill its main functional purpose - to satisfy the demand for electricity. Our task was to study Ukrainian power system resistance to systematic large scale missile and drone strikes. References 32, figures 8, tables 3.